SDGs-Based Religious Moderation in the School Environment: A Case Study of SMP Muhammadiyah 2 Denpasar, Bali - Hafidz; Nurul Latifatul Inayati; Arif Rahman; Nur Farid Khoiruddin (Profetika: Jurnal Studi Islam, 2024)
Objectives: This study aims to examine the implementation of religious moderation based on the Sustainable Development Goals (SDGs) at SMP Muhammadiyah 2 Denpasar, Bali, particularly in supporting SDG 4 and SDG 16. Theoretical framework: The research is grounded in the theoretical framework of religious moderation, multicultural education, and character education, which emphasizes balance, tolerance, inclusivity, and respect for diversity within educational institutions. Literature review:  A review of relevant literature indicates that schools play a strategic role in fostering moderate religious attitudes, especially in multicultural societies where globalization and digital media increasingly influence students’ perspectives and behaviours. However, empirical studies linking religious moderation explicitly to the SDGs in Indonesian school contexts remain limited. Method: Using a descriptive qualitative approach, this study collects data through in-depth interviews with teachers and students, classroom interaction observations, and analysis of school policy documents. The data are analyzed thematically to identify patterns and core themes related to practices of religious moderation, perceptions of tolerance, and multicultural engagement within the school environment. Results: The findings reveal that SMP Muhammadiyah 2 Denpasar integrates religious moderation through inclusive learning practices, intercultural interactions, school regulations promoting mutual respect, and the internalization of Islamic values aligned with peaceful coexistence. Teachers and students generally demonstrate positive attitudes toward diversity, although challenges persist due to external social and media influences that may trigger intolerance. Implications: The study highlights that the implementation of religious moderation contributes to strengthening students’ character, enhancing social harmony, and supporting the achievement of SDG-oriented education. Novelty: The novelty of this study lies in its explicit linkage between religious moderation practices and the SDGs within a Muhammadiyah school located in a Hindu-majority region, offering a contextual model for promoting peace-oriented and inclusive education in multicultural settings.